2006
DOI: 10.1136/bjo.2005.088104
|View full text |Cite
|
Sign up to set email alerts
|

The Antioxidants in Prevention of Cataracts Study: effects of antioxidant supplements on cataract progression in South India

Abstract: Aim: To determine if antioxidant supplements (b carotene and vitamins C and E) can decrease the progression of cataract in rural South India. Methods: The Antioxidants in Prevention of Cataracts (APC) Study was a 5 year, randomised, triple masked, placebo controlled, field based clinical trial to assess the ability of interventional antioxidant supplements to slow cataract progression. The primary outcome variable was change in nuclear opalescence over time. Secondary outcome variables were cortical and poster… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
1
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(26 citation statements)
references
References 56 publications
1
21
1
1
Order By: Relevance
“…Several nutrients, including antioxidants (3,8,9) and the carotenoid xanthophylls lutein and zeaxanthin (10-13), have been postulated to reduce cataract risk. Of the antioxidants included in our study, carotene and vitamins C and E were not associated with cataract risk, which was a finding that was in contrast to the inverse association generally shown in previous studies (3,(23)(24)(25)(26)(27)(28), although a fieldbased clinical trial in South India failed to show a benefit of antioxidant supplementation in slowing cataract progression (29).…”
Section: Discussioncontrasting
confidence: 56%
“…Several nutrients, including antioxidants (3,8,9) and the carotenoid xanthophylls lutein and zeaxanthin (10-13), have been postulated to reduce cataract risk. Of the antioxidants included in our study, carotene and vitamins C and E were not associated with cataract risk, which was a finding that was in contrast to the inverse association generally shown in previous studies (3,(23)(24)(25)(26)(27)(28), although a fieldbased clinical trial in South India failed to show a benefit of antioxidant supplementation in slowing cataract progression (29).…”
Section: Discussioncontrasting
confidence: 56%
“…No benefit was observed in the AREDS trial for high-dose antioxidant supplements ( ␤ -carotene, vitamin C and vitamin E) [61] or the VECAT study using highdose vitamin E [62] . Supplementation might be expected to have a stronger effect in an antioxidant-depleted population but a trial in southern India found no benefit from supplementation with multivitamins (vitamins A, C and E) on the rate of progression of opacities over a 5-year period [63] . However, a recently published trial in an Italian population using a broad-spectrum multivitamin/mineral supplement found a reduced rate of progression of nuclear opacities and an increased risk of posterior subcapsular opacities [64] .…”
Section: Epidemiological Evidence On Antioxidantsmentioning
confidence: 99%
“…2 This issue of the BJO (p 847) reports the results of a randomised clinical trial of antioxidant supplementation to prevent the onset and/or progression of cataract in south India. 3 The unfortunate news is that antioxidant supplementation had no impact on cataract progression in this population. Although such ''negative'' trials are often seen as disappointments, and sometimes the authors have difficulty getting the results published, it is important to know whether to bother to spend money and effort to provide supplements.…”
mentioning
confidence: 99%
“…Numerous cross sectional and cohort studies have documented strong associations between antioxidants intake (through food and/or supplements) and cataract, amply referenced in the paper by Gritz et al 3 However, only one randomised trial has been conducted previously in the developing world. 4 That study showed a reduction in the prevalence of nuclear cataract with certain micronutrient combinations, suggesting promise for such interventions.…”
mentioning
confidence: 99%